Polscy prawnicy emigracyjni o sowietyzacji prawa cywilnego - Fiedorczyk, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
After World War II many of Polish outstanding lawyers decided not to return to Poland. They refused to live behind the Iron Curtain, settling primarily in Great Britain and in the United States. They organized Polish Faculty of Law in London and established legal associations. They were trying to continue research on Polish law, which was changing rapidly in accordance with the principles of the Soviet model. The civil law was one of the topics of research. We should mention Zygmunt Nagórski, Kazimierz Grzybowski and Aleksander W. Rudziński as the most important researchers. They published their books and articles mostly in English. We can observe two different periods in the history of Polish civil law after World War II. During the first period Polish law was unified on the basis of Western standards. This process was met by emigration lawyers with high approval, although some inconsistent changes were also noticed and mentioned. In the second period, after 1948, the process of Stalinization of Polish law began. These changes were registered and analyzed very thoroughly. The opinions of Polish emigration lawyers remain valid even to this day and are generally confirmed by the historians of law.
Keywords: prawnicy; polska emigracja; prawo cywilne; sowietyzacja